Analisis Sistem Informasi Akuntansi Zakat Infaq Sedekah (ZIS) pada Lembaga Sosial Pesantren Tebuireng (LSPT) - Koyimah Koyimah; Ika Zutiasari (Prodi Akuntansi Fakultas Ekonomi Universitas Hasyim Asy'ari, 2020)
This study discusses the Zakat Accounting Information System, Infaq Alms (ZIS) at the Tebuireng Islamic Boarding School Social Institution (LSPT). This study aims to determine the accounting information system contained in the Social Institute of Islamic Boarding School Tebuireng (LSPT) and find out the suitability of the financial statements of LSPT with PSAK 109. This study uses descriptive qualitative research methods that describe the application of accounting information systems for the receipt and distribution of ZIS funds at the Tebuireng Islamic Boarding School Social Institution (LSPT) and described the application of ZIS PSAK 109 accounting with the ZIS LSPT accounting. Data collection techniques used are through observation: perfect participants and participants as observers, interviews: open / closed and structured interviews, then documentation. Data analysis techniques used are three processes, namely data reduction, data presentation and data verification. The results showed that the Tebuireng Islamic Boarding School Social Institution (LSPT) had used the ZIS accounting information system, namely the zakat application and ZIS management application for the PSAK 109 edition.